Firearms Effects on Tsimane’ Hunting and Traditional Knowledge in Bolivian Amazonia - Medinaceli, Armando; Quinlan, Robert J. (Ethnobiology Letters, 2018)
Subsistence hunting is a key activity for indigenous Amazonian people. Traditional Tsimane’ bow hunting was strongly affected by the introduction of firearms over 30 years ago. Tsimane’ of Bolivia maintain traditional hunting techniques with bows and arrows, sometimes in conjunction with modern firearms. This study explores Tsimane’ perceived costs and benefits of bow- versus gun-hunting. We consider cultural conservation in addition to factors typical in ecological comparisons of traditional and introduced hunting technologies. Firearms are expensive and less reliable than bows and arrows. Costs of purchasing firearms requires market engagement and surplus production to generate cash. Tsimane’ do not identify overhunting as one of the costs of firearms; though multiple studies show reduced game populations in areas under moderate to intense gun-hunting pressure. In sum, Tsimane’ identify multiple benefits to traditional hunting technology, while firearms have a strong effect of the loss of knowledge regarding fabrication of bows and arrows, and present a challenge to Tsimane’ cultural identity as bow-hunters.